A mídia e a Guerra do Iraque nos Estados Unidos - Elias, Paula de Campos [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This study aims to analyze the perception and positioning of the American newspaper The New York Times about the Iraq war led by George W. Bush in 2003. It will also approach the question of the relationship between media and government. The theoretical foundation of the work consists of the literature of the field of international relations, American foreign policy and political communication. The empirical part will involve the attempt to establish a correlation between the tone and content of the newspaper editorials and the president's popularity during the war

O presente trabalho tem por objetivo analisar a percepção e o posicionamento do jornal americano The New York Times sobre a Guerra do Iraque conduzida por George W. Bush em 2003. Também será trabalhada a questão da relação entre mídia e governo. O alicerce teórico do trabalho consiste de literatura do campo de relações internacionais, política externa americana e comunicação política. A parte empírica omplicará na tentativa de estabelecer uma correlação entre o tom e o conteúdo dos editoriais do referido jornal e a popularidade do presidente durante a guerra